2004
DOI: 10.1073/pnas.0307698100
|View full text |Cite
|
Sign up to set email alerts
|

The LTR enhancer of ERV-9 human endogenous retrovirus is active in oocytes and progenitor cells in transgenic zebrafish and humans

Abstract: The solitary LTRs of ERV-9 human endogenous retrovirus are middle repetitive DNAs associated with 3,000 -4,000 human gene loci including the ␤-globin gene locus where the ERV-9 LTR is juxtaposed to the locus control region (␤-LCR) far upstream of the globin genes. The ERV-9 LTRs are conserved during primate evolution, but their function in the primate genomes is unknown. Here, we show that in transgenic zebrafish harboring the ␤-globin ERV-9 LTR coupled to the GFP gene, the LTR enhancer was active and initiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 40 publications
1
55
0
Order By: Relevance
“…To determine if ERV-9 LTR was similarly expressed in Tg mice as in humans, we analyzed the transcription levels of ERV-9 LTR in various Tg mouse tissues. In humans, ERV-9 LTR is transcribed in the progenitor cells of erythroid and a number of other tissues and in oocytes and follicular granulosa cells (17). Similarly in Tg mice, ERV-9 LTR was transcribed at high levels in female germinal cells and erythroid and thymus progenitor cells (Fig.…”
Section: Expression Of Erv-9 Ltr In Erythroid Progenitor Cells and Gementioning
confidence: 85%
See 2 more Smart Citations
“…To determine if ERV-9 LTR was similarly expressed in Tg mice as in humans, we analyzed the transcription levels of ERV-9 LTR in various Tg mouse tissues. In humans, ERV-9 LTR is transcribed in the progenitor cells of erythroid and a number of other tissues and in oocytes and follicular granulosa cells (17). Similarly in Tg mice, ERV-9 LTR was transcribed at high levels in female germinal cells and erythroid and thymus progenitor cells (Fig.…”
Section: Expression Of Erv-9 Ltr In Erythroid Progenitor Cells and Gementioning
confidence: 85%
“…An exception was mouse sperms, which expressed ERV-9 LTR at a high level (Fig. 5), in contrast to human sperms (17). The generally similar expression patterns of the ERV-9 LTR in Tg mice and humans indicated that mouse transgenics can serve as an appropriate system to test the function of primate ERV-9 LTRs.…”
Section: Expression Of Erv-9 Ltr In Erythroid Progenitor Cells and Gementioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, the ERV9-LTR shows germline-specific promoter activity even in zebrafish, as shown by a transgene where this LTR drives the expression of a green fluorescent protein reporter. 55 The mechanisms that lead to testis-specific expression appear to involve the transcription factors NF-Y and Sp1, 56 but may also be governed by the expression of antisense transcripts. 57 In any case, the virus appears to take advantage of ancient mechanisms for testicular transcription, to push the expression of its own genome, but also to re-assort this promoter activity with novel cellular genes.…”
Section: Erv9-ltr-driven Cell Death U Beyer Et Almentioning
confidence: 99%
“…Interspersed repeats have been suggested to function as cis-acting transcription regulators in some circumstances. For example, the mouse beta globin LCR was shown to express an intergenic transcript from an LTR-ERV9 promoter, which is responsible for local chromatin remodeling (Pi et al 2004). In addition, SINE repeats have been reported to contain DHS at the imprinted Igf2/H19 region and at the nonimprinted Sprr locus (Moore et al 1997;Martin et al 2004).…”
Section: Dhs Mapping To Interspersed Repeatsmentioning
confidence: 99%